Numerical Investigation on Thermal Conductivity of Metal Nanoparticle Dispersed Composite Phase Change Materials - Kalidasan B.; Pandey A.K.; Rajamony R.K.; Chinnasamy S.; Buddhi D. (Malaysian Institute of Chemistry, 2025)
Phase change materials (PCMs) possess excellent property to store thermal energy effectively at low cost. Thermal energy storage (TES) using PCMs are of current research hotspot as they contribute towards a) effective thermal management b) heat dissipation in electronic gadgets c) peak energy shift in building and d) to increase the renewable energy mix. In spite of numerous benefits, PCMs suffer due to low thermal conductivity which highly influences the energy storage rate. In this research investigation, using the existing numerical model a) Parallel Model, b) Series Model, c) Maxwell Model and d) Hamilton Model, the author determine and evaluate the thermal conductivity of composite PCMs. Both organic and inorganic PCM were opted for analysis with metal nanoparticles. Numerically determining the thermal conductivity of PCM would provide a vital significance to the research before carrying out any experimental evaluation, which would be time and cost saving. The research article will also provide future outlooks on nanoparticle dispersed PCM with a focus on scientific problems and practical difficulties when there is a non-uniform dispersion of nanoparticle with PCM. ? 2024 Malaysian Institute of Chemistry. All rights reserved.